ANALISIS CEMARAN Coliform DAN Escherichia coli PADA GULA AREN CAIR DI PANTAI PANJANG, KOTA BENGKULU MELALUI PENDEKATAN METODE KIT DAN MPN - Hernety; Sipriyadi; Dwi Kurnia Putri; Oky Hermansyah; Rizqa Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Liquid palm sugar is a natural sweetener widely used in traditional beverages, particularly by coconut ice vendors in the Pantai Panjang area of Bengkulu City. The processing method, which is still carried out traditionally with inadequate sanitation, has the potential to cause contamination by Coliform and Escherichia coli bacteria. This study aims to analyze the presence of Coliform and Escherichia coli bacteria in liquid palm sugar using the KIT (Compact Dry EC) method and the Most Probable Number (MPN) method. This study is descriptive in nature, with a sample consisting of 10 liquid palm sugar samples collected from coconut ice vendors in Pantai Panjang, Bengkulu City. Testing was conducted using the KIT method as an initial screening and followed by the MPN method as a confirmatory test. The results showed that 2 out of 10 samples tested positive for Escherichia coli contamination based on the KIT method. Further testing using the MPN method revealed an index value of ≥1898 MPN/100 mL in one sample, while the other sample showed a value of 6 MPN/100 mL at the enrichment stage. A supplementary test using EMBA medium revealed the formation of metallic green colonies, indicating the presence of Escherichia coli. Based on these results, some of the liquid palm sugar samples did not meet food safety standards as defined by SNI, posing a potential health risk to consumers.